Nurjanah, Khususiyah, Gumilang KEEFEKTIFAN KONSELING KELOMPOK REALITA TEKNIK WDEP UNTUK MENINGKATKAN KEDISIPLINAN PESERTA DIDIK KELAS VIII SMP ISLAM TANEN REJOTANGAN TAHUN PELAJARAN 2016/2017 - Nurjanah, Ana (Universitas Nusantara PGRI Kediri, 2017)
ABSTRACT Counseling is one of the realities group counseling approach that can reduce student discipline violations are marked with a violation in terms of physical and violation of terms of behavior. With the reality of group counseling is expected students will be responsible for himself and become a person who does not ignore from the 3-R (right, Responsibility, reality). The purpose of this study was to obtain accurate information and data on the effectiveness of group counseling to improve discipline reality of class VIII SMP Islam Tanen Rejotangan Odd Semester Academic Year 2016/1017. This study used a technique quasy-experimental design (quasi-experimental) with a quantitative approach with research subjects eighth grade students of SMP Islam Tanen Rejotangan number of 10 students, divided into 2 groups: 5 students of grade control and 5th grade students experiment. The research was conducted in five counseling sessions, using the instrument scale pretest and posttest discipline students' concentration. The results of the final data analysis is done by using a non-parametric statistical tests Wilcoxon signed rank test with the Sig. (2-tailed) 0.043 N 5 and probabilities indicate that the 0.05 level. As well as the probability value 0.043 <0.05, consequently Ha accepted and H0 is rejected, which means there is no difference between the control and experimental classes. Based on the research that has been done suggestions that should be mentioned is should the teacher guidance and counseling can be used as source materials science to improve the quality of guidance and counseling. Key words: Reality Group Counseling, Discipline of Students.